Synthesis of Alumatrane and It's Application as Gelling Agent in Lithographic Ink Formulations - Nemati Kharat, Ali; Karimi, Safieh (Asian Journal of Chemistry, 2010)
Aluminum alkoxides modified with alkanolamines has been used in wide range of applications in industry, such as textile-treating agents, gelling agent in lithographic inks, paints and other coatings. In this work sample of triethanolamine aluminates were prepared from aluminum isopropoxide and aluminum hydroxide and their ability to build up stable gel was examined in lithographic ink formulation and then qualities were compared to commercial samples. All samples were characterized by FT-IR, 27Al NMR, TGA and elemental analysis. For investigation of effect of alkoxide precursor on quality of sol-gel dried alumina, some of prepared alkoxides were hydrolyzed in different conditions. BET of some samples show better surface area, respect to previously reported methods of sol-gel derived alumina.